2014
DOI: 10.1038/srep07370
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Quantitative Analysis of Painting Arts

Abstract: Scientists have made efforts to understand the beauty of painting art in their own languages. As digital image acquisition of painting arts has made rapid progress, researchers have come to a point where it is possible to perform statistical analysis of a large-scale database of artistic paints to make a bridge between art and science. Using digital image processing techniques, we investigate three quantitative measures of images – the usage of individual colors, the variety of colors, and the roughness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 17 publications
1
52
0
1
Order By: Relevance
“…In natural language, for example, a few words appear with very high frequency, such as pronouns, while a great many are rare, such as the names of species of trees, but any sample will nevertheless tend to contain several rare words (111). A similar pattern is found in the distribution of colors among paintings in a given period of art history (112). In music, Zipf's law has been observed in We found that both the worldwide melodic and rhythmic bigram distributions followed power laws ( Fig.…”
Section: Melodic and Rhythmic Bigrams Are Distributed According To Pomentioning
confidence: 80%
“…In natural language, for example, a few words appear with very high frequency, such as pronouns, while a great many are rare, such as the names of species of trees, but any sample will nevertheless tend to contain several rare words (111). A similar pattern is found in the distribution of colors among paintings in a given period of art history (112). In music, Zipf's law has been observed in We found that both the worldwide melodic and rhythmic bigram distributions followed power laws ( Fig.…”
Section: Melodic and Rhythmic Bigrams Are Distributed According To Pomentioning
confidence: 80%
“…A recent development that is proving to have far-reaching implications for a scientific exploration of human actions and behavior in many social, cultural complex systems is the increasing availability of massive high-quality data that allows a large-scale application of scientific frameworks and verifi-cation [2][3][4][5][6][7]. In the area of culture, subjects on which quantitative pattern-finding have been performed to a degree include literature [8][9][10][11][12] where Polish linguist Wincenty Lutosławski's work on the statistical features of word usage in Plato's Dialogue [8] is well known, music [13][14][15][16][17], and painting [18][19][20][21][22][23][24][25][26]. A landmark scientific study of paintings can be found in Taylor et al's characterisation of Jackson Pollock's ) drip paintings using fractal geometry to distinguish between authentic Pollocks and those of unknown origins [18], demonstrating that an artistic style can be quantified.…”
Section: Introductionmentioning
confidence: 99%
“…A landmark scientific study of paintings can be found in Taylor et al's characterisation of Jackson Pollock's ) drip paintings using fractal geometry to distinguish between authentic Pollocks and those of unknown origins [18], demonstrating that an artistic style can be quantified. More recent examples regarding painting include Lyu et al's wavelet-based decomposition of images [20], Hughes et al's sparse-coding models for authenticating artworks [21], Kim et al's characterization of variations in chiaroscuro technique via the so-called "roughness exponent" from statistical physics [22] and Gatys et al's style representation derived from correlations between the different features in different layers in a Convolutional Neural Network [23]. Besides quantification of artistic styles, some studied perceived similarities between different paintings [24], the influence relationships between artworks for quantifying creativity in an artwork [25], and the changes in the perception of beauty using face-recognition on images from different eras [26].…”
Section: Introductionmentioning
confidence: 99%
“…It is also helpful for a therapist with a short-term experience. The effectiveness of such quantitative analysis has been recently reported in many researches for artistic paintings [4].…”
Section: Introductionmentioning
confidence: 99%